2016
DOI: 10.1016/j.fertnstert.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanoparticles as a new approach to improve the efficacy of gene therapy against differentiated human uterine fibroid cells and tumor-initiating stem cells

Abstract: Uterine fibroid(s) (UF/UFs) are benign tumors commonly found in women of reproductive age. The long-term outcomes of myomectomies are often hampered by high rates of recurrence (up to 60%). Objective To study whether efficient transduction and subsequent elimination of fibroid tumor initiating stem cells during debulking of tumor cells will aid in completely eradicating the tumor as well as decreasing the likelihood of recurrence. Design We have developed a localized non-surgical adenovirus-based alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 70 publications
0
26
0
1
Order By: Relevance
“…Measurement data from the ZetaView were analyzed using the corresponding software, ZetaView 8.02.28, and Microsoft Excel 2013 (Microsoft Corp., Seattle, WA, USA). As described previously, we selected the mode as the measurement for size in our analysis [13, 32, 48, 49]. The mode, also referred to as the diameter, is defined as the size of the most abundant particles.…”
Section: Methodsmentioning
confidence: 99%
“…Measurement data from the ZetaView were analyzed using the corresponding software, ZetaView 8.02.28, and Microsoft Excel 2013 (Microsoft Corp., Seattle, WA, USA). As described previously, we selected the mode as the measurement for size in our analysis [13, 32, 48, 49]. The mode, also referred to as the diameter, is defined as the size of the most abundant particles.…”
Section: Methodsmentioning
confidence: 99%
“…In the emerging field of nanotechnology, nanoparticle platforms have also demonstrated great potential for detection, diagnosis, and treatment of human infertility. Most reports have explored the use of nanomaterials for the detection and therapy of reproductive cancers and noncancer conditions, such as uterine leiomyoma (Shalaby et al, ) and endometriosis (Liu et al, ; Zhao et al, ). However, a growing number of studies have applied nanotechnology in reproductive biology to target and sort specific populations of gametes and to optimize gene transfer and editing methodologies (Barkalina, Charalambous, Jones, & Coward, ; Remião et al, ).…”
Section: Nanotechnologymentioning
confidence: 99%
“…In the emerging field of nanotechnology, nanoparticle platforms have also demonstrated great potential for detection, diagnosis, and treatment of human infertility. Most reports have explored the use of nanomaterials for the detection and therapy of reproductive cancers and noncancer conditions, such as uterine leiomyoma (Shalaby et al, 2016) and endometriosis Zhao et al, 2016).…”
Section: Nanotechnologymentioning
confidence: 99%
“…56 Recently, Shalaby and colleagues demonstrated that magnetic nanoparticles complexed to the suicide gene system significantly increased transduction efficiency and that the inhibitory effects of the system were maintained, suggesting that the use of nanoparticles could lower the total viral dose needed for a desired effect. 57 From these studies, it appears that nanoparticles can be used to target fibroids and therefore improve treatment efficacy.…”
Section: Nanoparticles and Targeted Therapymentioning
confidence: 99%